ASSOCIATION BETWEEN VARIATIONS IN SELLA TURCICA DIMENSIONS AND MORPHOLOGY AND SKELETAL MALOCCLUSIONS - Afzal, Erum; Fida, Mubassar (Journal of Ayub Medical College Abbottabad, 2019)
Background: The growth of sella turcica is completed early in life, therefore it can be used as a stable landmark for the prediction of future skeletal malocclusions. This early diagnosis may help in planning less complicated treatment modalities. Therefore, this study aimed to evaluate the relationship between sella turcica dimensions and morphology with various skeletal patterns. Methods: A cross sectional study was conducted using the pre-treatment cephalograms of 180 subjects aged 13-19 years. The subjects were divided into two groups based on skeletal patterns. The dimensions of sella turcica and skeletal patterns were digitally measured using View Pro-X software. One-way ANOVA was applied to compare sella turcica dimensions among skeletal patterns. Sella dimensions and vertical growth patterns were compared using Post-hoc Tukey test. Chi-square test was applied to compare sella morphology among malocclusion groups. Results were taken as statistically significant at p-value of ‰¤0.05. Results: Sella dimensions showed insignificant differences among sagittal groups whereas, significant differences were found for sella length (p ‰¤0.02) and depth (p ‰¤0.03) among the vertical groups. Multiple comparisons showed significant differences between sella length (p ‰¤0.03) and diameter (p ‰¤0.04) between normodivergent versus hyperdivergent groups. Moreover, significant differences were found in the sella turcica morphology among sagittal malocclusion (p ‰¤0.03). Conclusions: Increased dimensions of sella turcica were associated with hyperdivergent growth pattern. Bridging of the sella turcica was found to be prevalent in class III malocclusion. Keywords: Sella Turcica; Maxillofacial Development; Vertical Dimension; Malocclusion